Amomum villosum Lour. Fruit extract mitigates hyperlipidemia through SREBP-2/LDLR/HMGCR signaling in high-cholesterol diet-fed mice - Ye-Seul Kim; Ha-Rim Kim; Paulrayer Antonisamy; Young-Rae Lee; Guemsan Lee; Hyun-Jong Jung; Kang-Beom Kwon (Journal of King Saud University: Science, 2022)
Amomum villosum Lour. (Zingiberaceae) is an herbal medicine used in Asian countries for various ailments. In the current experiment, the effect of AV water extract (AVE) on cholesterol-lowering capabilities along with its essential bio-molecular mechanisms have been examined. The efficiency of AVE against high-cholesterol diet (HCD)-generated hyperlipidemia was investigated using C57BL/6 mice. Mice have been divided to six categories: control group (normal diet), high-cholesterol diet (HCD), and HCD treated with AVE at 100, 200, and 500 mg/kg, or simvastatin 40 mg/kg for four weeks. AVE treated animal groups (100, 200, 500 mg/kg) had markedly lessened body mass increase (p < 0.01) and also had reduced liver and epididymal fat weights (p < 0.05) related to HCD alone batch. Hepatic TG levels in AVE 100 mg/kg, 200 mg/kg, and 500 mg/kg treated groups were meaningfully reduced by 13.32%, 14.61%, and 21.78%, respectively; and serum TG decreased by 25.65%, 31.97%, and 32.22%, respectively, compared to the HCD alone group. Serum TC was reduced by 11.17%, 12.48%, and 26.85% with AVE at 100, 200, and 500 mg/kg, respectively; and serum LDL-C declined by 10.08%, 18.50%, and 30.90% (p < 0.05) with AVE at 100, 200, and 500 mg/kg, respectively. Levels of mRNA expression including LDL receptor (LDLR), sterol regulatory element-binding protein 2 (SREBP2), and HMG-CoA reductase (HMGCR) were noticeably amplified by AVE (500 mg/kg) treatment. Similarly, AVE treatment significantly increased Hmgcr protein expression levels in a dose related fashion. These outcomes show that AVE displays a hypolipidemic effect and might function as a novel hypolipidemic therapy, further; they suggest a mechanism of action for this effect.